Spectral data of aqueously and thermally altered carbonaceous chondrites - Bates, H; Bates, H; Donaldson Hanna, K; Donaldson Hanna, K; King, A; King, A; Bowles, N; Bowles, N; Russell, S; Russell, S (University of Oxford, 2021)
Spectral data created as part of a study into the effects of aqueous and thermal alteration on the spectral signature in the NIR and MIR wavelength ranges. NIR data were collected as reflectance and MIR data were collected as emissivity under both ambient and simulated asteroid environment (SAE) conditions.